Organizational Communication at the Tanjung Batu Village Office, Ogan Ilir Regency in Improving Public Services - Ade Setiawan; Sepriadi Saputra; Badarudin Azarkasi (Universitas Muhammadiyah Palu, 2026)
This research highlights the urgency of improving the quality of public services at the Tanjung Batu Village Office, where there are still communication gaps, limited coordination, and unclear information flows that affect service performance. This research aims to examine how organizational communication is applied and how its role is in improving public services. The main questions of the research focus on the communication patterns that take place and their contribution to service improvement. Using a qualitative approach and case study design, data was collected through observation, in-depth interviews with staff, village heads, and the community, and documentation. Data analysis is carried out through reduction, presentation, and conclusion drawn. The results of the study show that communication occurs vertically, horizontally, and diagonally, but is still constrained by weak feedback systems, inconsistent coordination, and lack of use of digital information media. The improvements found include simplifying procedures, improving employee coordination, and increasing responsiveness to community needs. These findings confirm that effective organizational communication improves reliability, transparency, and responsiveness in public services.